2021
DOI: 10.3390/molecules26071952
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Rational Design of New Appended 1,2,3-Triazole-uracil Ensembles as Promising Anti-Tumor Agents via In Silico VEGFR-2 Transferase Inhibition

Abstract: Angiogenesis inhibition is a key step towards the designing of new chemotherapeutic agents. In a view to preparing new molecular entities for cancer treatment, eighteen 1,2,3-triazole-uracil ensembles 5a–r were designed and synthesized via the click reaction. The ligands were well characterized using 1H-, 13C-NMR, elemental analysis and ESI-mass spectrometry. The in silico binding propinquities of the ligands were studied sequentially in the active region of VEGFR-2 using the Molegro virtual docker. All the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In previous studies, hybrids of uracil with heterocycle groups were reported as potent compounds for cytotoxic activity. For example, compound A is a hybrid of uracil and oxadiazole with IC 50 = 0.88 μM against a studied cancer cell line [ 13 ], and compound B, bearing uracil and 1,2,3-triazole exhibited a promising cytotoxic with IC 50 = 4.5 and 7.7 μM against Hela and Huha cell lines respectively [ 31 ]. According to the stated items, 3-methyl–pyrimidine-2,4-dione was conjugated with various azole rings bearing benzyl or benzoyl substitution at the N-1 position of uracil with different electronic profiles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, hybrids of uracil with heterocycle groups were reported as potent compounds for cytotoxic activity. For example, compound A is a hybrid of uracil and oxadiazole with IC 50 = 0.88 μM against a studied cancer cell line [ 13 ], and compound B, bearing uracil and 1,2,3-triazole exhibited a promising cytotoxic with IC 50 = 4.5 and 7.7 μM against Hela and Huha cell lines respectively [ 31 ]. According to the stated items, 3-methyl–pyrimidine-2,4-dione was conjugated with various azole rings bearing benzyl or benzoyl substitution at the N-1 position of uracil with different electronic profiles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virtual molecular docking studies were used to investigate the inhibitory potential of produced compounds [29]. Virtual screening was performed using Molegro Virtual Docker (MVD), which was installed on an Intel Core i7 9700k processor with 120 GB SSD, 1 TB hard drive, and an NVIDA GeForce GTX 1050 graphics card [30,31].…”
Section: Molecular Docking Methodologymentioning
confidence: 99%
“…8a showed six hydrogen bond interactions along with six different types of interactions comprising VdW, hydrogen bond, pi-donor, pi-lone pair, and alkyl interactions with dihydropteroate synthetize. Antifolate showed total four hydrogen bond interactions [31].…”
Section: Albicansmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the report stating that 5-FU inhibits VEGF-mediated angiogenesis is noteworthy [ 47 ]. According to Reddy et al [ 48 ], 5-FU interacts with the VEGFR-2 active site through the formation of conventional hydrogen bonds by the –NH and carbonyl groups of the uracil moiety with Glu885 (2.37 Å) and Asp1046 (2.03 Å), respectively. Cisplatin, on the other hand, is particularly effective in treating various types of lung cancer [ 49 ].…”
Section: Introductionmentioning
confidence: 99%